Case let: Growth of collective bargaining business models in India - Chauhan, Meenal; Pachpore, Pranjal (Gyan Management Journal, 2012)
Online shopping is a new business model emerging in £-Commerce world and becoming quite popular in recent y_ears. Online shopping website is where people can recommend their favorite products for others to discover and purchase on line. Online shopping combines Business-to-Business, Business-toConsumers and Consumers-to-Consumers services together. The goal of this study is to analyze the business model of the case company and compare its business model with its selected main competitors in order to find out the success factors for an on line shopping company in the fiercer competition.
Keywords: business model; website; products; company; competitors